The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.3762/bjnano.10.241
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of click chemistry microarrays for immunosensing of alpha-fetoprotein (AFP)

Abstract: The level of cancer biomarkers in cells, tissues or body fluids can be used for the prediction of the presence of cancer or can even indicate the stage of the disease. Alpha-fetoprotein (AFP) is the most commonly used biomarker for early screening and diagnosis of hepatocellular carcinoma (HCC). Here, a combination of three techniques (click chemistry, the biotin–streptavidin–biotin sandwich strategy and the use of antigen–antibody interactions) were combined to implement a sensitive fluorescent immunosensor f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…found that click chemistry combining with the biotin‐streptavidin‐biotin sandwich design and the antigen‐antibody interactions could realize a sensitive fluorometric immunosensor for AFP detection ( Figure ). [ 39 ] The anti‐AFP antibody was immobilized onto the surfaces of sandwich using the biotin‐streptavidin‐biotin protein fixation technique. The fluorescent labeled AFP was detected by microchannel cantilever spotting to evaluate the sensing performance based on the optimal microarray.…”
Section: Nanoparticle‑based Hcc Surveillancementioning
confidence: 99%
See 1 more Smart Citation
“…found that click chemistry combining with the biotin‐streptavidin‐biotin sandwich design and the antigen‐antibody interactions could realize a sensitive fluorometric immunosensor for AFP detection ( Figure ). [ 39 ] The anti‐AFP antibody was immobilized onto the surfaces of sandwich using the biotin‐streptavidin‐biotin protein fixation technique. The fluorescent labeled AFP was detected by microchannel cantilever spotting to evaluate the sensing performance based on the optimal microarray.…”
Section: Nanoparticle‑based Hcc Surveillancementioning
confidence: 99%
“…Reproduced with permission. [ 39 ] Copyright 2019, Beilstein Institute for the Advancement of Chemical Sciences. ii) Multifunctional ultrasound nanobubbles for HCC visualization.…”
Section: Introductionmentioning
confidence: 99%
“…For this, molecules that have specific affinity with the protein in question (bioreceptors) should be immobilized on a surface (transducer). [29][30][31] In previous works, we prepared microarrays of dyes containing azide or thiol groups on DBCO-terminated glass surfaces [32] and dyes containing maleimide or DBCO groups on thiol-terminated glass surfaces [33] using microchannel cantilevers spotting (μCS). In order to enable even more flexible choice of immobilization chemistry, in this work, three different routes for the surface functionalization of epoxy-terminated glasses will be examined.…”
Section: Introductionmentioning
confidence: 99%
“…For this, molecules that have specific affinity with the protein in question (bioreceptors) should be immobilized on a surface (transducer). [29][30][31] In previous works, we prepared microarrays of dyes containing azide or thiol groups on DBCO-terminated glass surfaces [32] and dyes containing maleimide or DBCO groups on thiol-terminated…”
Section: Introductionmentioning
confidence: 99%
“…It has to be noticed that surface modification by mean of click chemistry has already been investigated in the literature. Notably, Dadfar et al has notably extensively studied thiol terminated surface modifications by comparing thiol-ene and thiolyne click reactions, [13] deposition of protein microarray via thiol, amine and azide functionalities for biosensor applications, [14] click reaction of alpha fetoprotein for immunosensing [15] and catalyst free click reaction for biomedical and biological applications. [16] The redox functional group selected in this study is ferrocene, which is extensively used for the formation of SAMs but also for its unique redox properties for various applications.…”
Section: Introductionmentioning
confidence: 99%